2021
DOI: 10.1002/jbmr.4424
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Proliferating Osteoblast Lineage Cells After Fracture Leads to Atrophic Nonunion in a Mouse Model

Abstract: Nonunion is defined as the permanent failure of a fractured bone to heal, often necessitating surgical intervention. Atrophic nonunions are a subtype that are particularly difficult to treat. Animal models of atrophic nonunion are available; however, these require surgical or radiation‐induced trauma to disrupt periosteal healing. These methods are invasive and not representative of many clinical nonunions where osseous regeneration has been arrested by a “failure of biology”. We hypothesized that arresting os… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…In vivo , following implantation at 4 weeks, 50% or less of the animals treated with either scaffold only or the sham control had a complete radiographic bridging at 12 weeks. This blunted healing response was consistent with our previous study that established the Col1-tk atrophic non-union model ( Hixon et al, 2021 ). Comparatively, the radiograph analysis showed that the scaffolds seeded with GFP + cells and the scaffolds seeded with cells producing BMP-2 were the only groups that reached complete bridging in all the animals by the end of 12 weeks.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In vivo , following implantation at 4 weeks, 50% or less of the animals treated with either scaffold only or the sham control had a complete radiographic bridging at 12 weeks. This blunted healing response was consistent with our previous study that established the Col1-tk atrophic non-union model ( Hixon et al, 2021 ). Comparatively, the radiograph analysis showed that the scaffolds seeded with GFP + cells and the scaffolds seeded with cells producing BMP-2 were the only groups that reached complete bridging in all the animals by the end of 12 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…We recently demonstrated a model of atrophic non-union in Col1-tk mice dosed with GCV ( Hixon et al, 2021 ). Briefly, a previously established protocol was employed to create a full fracture in the right femur of 12-week-old mice ( Gardner et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations